Business strategy, overvalued equities, and stock price crash risk - Habib, A.; Hasan, Mostafa (J A I Press, 2017)
This paper examines empirically the effect of firm-level business strategies on future stock price crash risk, and the extent to which equity overvaluation moderates this relation. By exploring the extent to which firms following particular business strategies are more or less likely to experience crash risk, we provide evidence that increases our understanding of the underlying determinants of crash risk. Using a composite strategy score developed by Bentley, Omer and Sharp (2013) and applying two variants of crash risk, we document that firms following innovative business strategies (prospectors) are more prone to future crash risk than defenders. We also find that prospectors are more prone to equity overvaluation which, in turn, increases future crash risk.